Empowering MSMES in Sumerta Kauh Village to Support Decent Work and Economic Growth - Ni Made Vita INDRIYANI; I Gst. B. Ngr. P. PUTRA (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
The development of micro, small, and medium enterprises (MSMEs) is the goal of multi-stakeholder partnerships. In the context of business groups, these partnerships will provide access to resources, knowledge, and broader networks. The partnership program aims to empower MSMEs in Sumerta Kauh Village. Sumerta Kauh Village is located in the East Denpasar District, Denpasar City, Bali Province. MSMEs in Sumerta Kauh Village are skilled in making Balinese snacks, but their production process is not continuous. Production. This program is implemented through training provided by experts. Experts first understand the manufacturing process for MSME products. After that, training is provided, providing materials on production and packaging. It is because the majority of group members work in offices, resulting in the group's suboptimal performance. Several issues exist within MSMEs, including: 1) Monotonous production and a lack of innovation, 2) Poorly organized accounting records, and 3) Lack of training and outreach for human resource development. Therefore, empowerment of MSMEs in Sumerta Kauh Village is necessary to support decent work in line with MSME objectives and to increase MSME economic growth.